SOME HISTORICAL ASPECTS OF OPERATING AND RESEARCH ACTIVITIES - Літвінова, Ірина Феофанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: for understanding the origins, historical background of the formation and development of private detective activity to explore some of the historical aspects of search operations. Results: it has been established that since its inception, the state has tried to monopolize search activities in its own interests, and therefore the vast majority of historical material is devoted to the state search (intelligence, counterintelligence, political and criminal investigation). Along with this, a separate (non-state) search in its various manifestations and forms has existed and continues to exist separately from the state since ancient times. Thus, it turns out that the state investigation on the basis of which the science of «operative-search activity» (hereinafter – OSA) subsequently emerged and private detective activity are interrelated social phenomena and have one common history, since the first originated the second. In addition, the methods used today in OSA are almost identical to the methods used by private detectives in their professional activities. Thus, for understanding the origins, historical prerequisites for the formation and development of private detective activity some historical aspects of operational and search activities also should be investigated. Discussion: state investigation on the basis of which the science of «operative-search activity» subsequently emerged and private detective activity are interrelated social phenomena and have one common history, since the first originated the second (the methods used today in OSA are almost identical to the methods used by private detectives in their professional activities).